IMPLEMENTATION OF ACTIVE LEARNING TWO STAY TWO STRAY COOPERATIVE MODEL IN SOCIAL STUDIES - Seno Budhi Ajar; Nur Dawam (Universitas Sebelas Maret (UNS), 2021)
In the 2013 curriculum, learning is focused on student centers or known as active learning. This study aims to determine the obstacles faced in implementing active learning two stay two stray cooperative model and their effects on social studies outcomes of junior high school students. This research is a classroom action research with research subjects in the form of 8th grade students of Surakarta 9th Junior High School, Surakarta City, Central Java Province. The research method used in data collection is a participant observation method in which the researcher acts as a teacher to find out the obstacles when implementing active learning two stay two stray models and the test method is used to measure the ability of student learning outcomes. The data analysis technique used is comparative descriptive analysis and critical analysis. The results of this study are (1) there are four aspects that become obstacles when applying active learning two stay two stray cooperative model in social studies subjects namely aspects of time management, classroom management, learning resources, and student activity. (2) active learning two stay two stray cooperative model very effective in improving student learning outcomes.